A realist evaluation of post-implementation modifications: a context-initiative-mechanism-outcome perspective. - Oseni, Taiwo; Rahim, Mahbubur; Foster, Susan (Journal of Critical Realism, 2023)
This paper exemplifies a theoretical and methodological evaluation of IT Initiatives. It discusses post-implementation modifications (ERP-PIM) to enterprise resource planning (ERP) systems for the purpose of business process optimization (BPO) from a Context-Initiative-Mechanism-Outcome (CIMO) perspective. CIMO suggests that context and mechanisms are factors triggering causal effects responsible for outcomes derived from technology initiatives. Through conceptualization, data collection/analysis, and retroduction, the paper proposes a middle-range theory to facilitate the explanation of outcomes from diverse post-implementation initiatives. Data from multiple case study identifies situational and action-formation mechanisms, and actions as essential to realizing the desired outcomes. The proposed ERP-PIM-CIMO theory encapsulates: (i) Business Process Optimization (BPO) as context, (ii) ERP-PIM as structure, (iii) Business Process Efficiency, Effectiveness, and Flexibility as observable events, (iv) ERP capability as causal mechanism, (v) actions as necessary for the actualization of mechanism, and finally (vi) effort and cost, knowledge, and training as factors influencing actualization.